REVITALISASI SARANA DI KOTA TUA KECAMATAN KARIMUN KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Ariyoga, Ananto; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purposed to see the revitalization of facilities as well as see the rise of tourist visits in the old town Karimun sub-district of Karimun Regency, Riau Islands province, Due a tourist destination shaped of cultural heritage in Karimun Regency. This research used Yoetiâs theory (1996) about the tourism facilities as companies that provide services to tourists, either directly or indirectly and live life a lot depends on arrival of tourists. Used qualitative descriptive methode to analyzed the problems. The sample in this research were 11 sample by using snowball sampling. Amd then technique to collected the data in this research were using by observation, interview and documentation. Based on this research, revitalization of means in the old town Karimun sub-districts, Karimun Regency, Riau Islands Province, has been no correct management so that the revitalization of the old town as tourist destination need be implemented by the establishment of better programs and to establish local regulations concerning cultural heritage sites. Key Word: Revitalization of Facilities, Arrival of Tourist, Karimun Sub-district